Occupational Stress in the Indian Army Oncology Nursing Workforce: A Cross-sectional Study - Neelam Sharma; Puneet Takkar; Abhishek Purkayastha; Pradeep Jaiswal; Sachin Taneja; Nishant Lohia; Anu Rani Augustine (Elsevier, 2018)
Objective: This cross-sectional, quantitative epidemiological study was aimed at finding out the degree of work-related stress among the staff nurses working in oncology. Methods: This study was conducted on 81 out of 100 oncology-trained nurses working in various oncology centers of Indian Army who consented to participate in it. It was carried out in five oncology centers of our organization where oncology-related facilities are available. Predesigned and pretested questionnaire covering their sociodemographic variables in part I and professional life stress scale by David Fontana in part II. The association between stress and various variables was found using Chi-square test. Results: Risk for professional stress was found more among unmarried young respondents of 20-30 years age group. No statistically significant association (P < 0.131) was found between department of posting and level of stress. Nurses reported that they had no time for rest, of whom 62.96% were suffering from moderate range of stress for a busy professional while only one admitted to have severe stress requiring remedial action. While 82.7% felt that they are able to achieve major objectives in life, 71.6% of them reported that they feel inadequately valued for their commitment at work. Conclusions: The main nurses' occupational stressors were criticism, feeling of not being appreciated for hard work, and having time for self. This type of assessment should be carried out in all hospitals so that working conditions for this important component of health care can be improved.